Communication Transformation: The Role of AI in Digital Public Relations Across Industries - Olivia Ridheta Citrawijaya (Universitas Multimedia Nusantara, 2024)
Artificial Intelligence (AI) in the world of Digital Public Relations (PR) is revolutionizing communication strategies across various industries, including manufacturing, healthcare, and finance, offering more personalized and efficient methods of communication. This research aims to explore the transformative potential of AI in the world of Public Relations (PR), with a focus on its impact on communication strategies, audience engagement, and content creation. This research uses the diffusion of innovation theory to analyze the adoption and utilization of AI technology in various sectors. Using a qualitative approach, this study adopts literature review and library research methods to analyze existing studies, reports, and practice case examples to provide in-depth insights into the application of AI in communication practices. The findings of this study show that AI improves data analysis capabilities, enables more targeted communication strategies, improves customer experience by providing personalized communication and 24/7 support through chatbots and virtual assistants and improves operational efficiency. The study highlights the importance of ethical use of AI and the development of digital skills to be able to fully harness the potential of AI in PR. The study contributes by offering a comprehensive understanding of the role of AI in transforming PR practices, providing insights for practitioners and policymakers on integrating AI into communication strategies. The integration of AI in PR highlights the transformative potential of AI in digital PR and the need to create rules and guidelines to ensure AI is used ethically and responsibly in PR. Also, there needs to be more research on exploring the impact of AI on communication ethics and developing a framework to ensure effective AI integration in PR.